Effectiveness and cost-effectiveness of a home-based functional exercise programme for community-dwelling frail older adults, ACTIVE-AGE@home, provided by professionals and volunteers: protocol of a pragmatic randomised controlled trial - Wim Peersman; Lieven Annemans; Dominique Van de Velde; Patricia De Vriendt; David Beckwée; Dimitri Vrancken; Elke De Smedt; Jade Tambeur; Emma De Keyser; Elise Vanbeuren; Siddhartha Lieten (BMJ Open)
Ethics and dissemination Ethics approval has been obtained from the Medical Ethics Committee of UZ Brussel (O.G. 016), Peer reflection group Biomedical Ethics, Laarbeeklaan 101, 1090 Brussels. Results will be disseminated in publications and other relevant platforms. This study was registered at Clinicaltrials.gov on 6 July 2023 and posted on 14 July 2023 after National Library of Medicine quality control review. Registration details: NCT05946109Trial registration number NCT05946109.